2017
DOI: 10.1096/fj.201601294r
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Sirt6 inhibition improves glucose tolerance in a type 2 diabetes mouse model

Abstract: Sirtuin 6 (SIRT6) is a sirtuin family member involved in a wide range of physiologic and disease processes, including cancer and glucose homeostasis. Based on the roles played by SIRT6 in different organs, including its ability to repress the expression of glucose transporters and glycolytic enzymes, inhibiting SIRT6 has been proposed as an approach for treating type 2 diabetes mellitus (T2DM). However, so far, the lack of small-molecule Sirt6 inhibitors has hampered the conduct of studies to assess the viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 26 publications
2
74
1
1
Order By: Relevance
“…This compound was administered for 10 days and results indicated an improvement in glucose regulation via oral glucose tolerance test (OGTT) leading the researchers to conclude that small molecule inhibitors of SIRT6 may be a functional strategy in the improvement of glycemic control for type 2 diabetics. In addition to these positive findings, there was also a notable increase in glucose transporters as well as reduced levels of insulin, triglycerides and cholesterol observed in the same study possibly paving way for small molecule inhibition of SIRT6 for other diseases as well [89].…”
Section: Pharmacological Intervention With Small Molecule Sirt6 Inhibsupporting
confidence: 52%
“…This compound was administered for 10 days and results indicated an improvement in glucose regulation via oral glucose tolerance test (OGTT) leading the researchers to conclude that small molecule inhibitors of SIRT6 may be a functional strategy in the improvement of glycemic control for type 2 diabetics. In addition to these positive findings, there was also a notable increase in glucose transporters as well as reduced levels of insulin, triglycerides and cholesterol observed in the same study possibly paving way for small molecule inhibition of SIRT6 for other diseases as well [89].…”
Section: Pharmacological Intervention With Small Molecule Sirt6 Inhibsupporting
confidence: 52%
“…No specific small molecule inhibitors of SIRT6 had been identified at the time of this study. However, one SIRT6 inhibitor was recently identified by Sociali et al; this SIRT6 inhibitor improves glucose tolerance in a mouse model of type 2 diabetes (27). Another report showed that the SIRT3-specific inhibitor, LC-0296, inhibits cell survival and proliferation, and promotes apoptosis of head and neck cancer cells.…”
Section: Silencing Sirtuin 6 (Sirt6) Blocks Proliferation and Promotementioning
confidence: 99%
“…Nevertheless, various studies have documented that both inhibition and enhancing SIRT6 may improve glucose tolerance in T2D. In murine model of T2D, inhibition of SIRT6 for ten days resulted in overexpression of muscular GLUT-1 and GLUT-4, enhanced glycolysis, decreased serum insulin as well as blood lipid concentrations and improved oral glucose tolerance [43]. On the other hand, experimental studies provided strong evidence for SIRT6 in pancreatic β-cells function [44,45].…”
Section: Discussionmentioning
confidence: 99%